Fabrication and laser operation of Yb:Lu2O3 transparent ceramics from co‐precipitated nano‐powders. Issue 12 (11th July 2019) - Liu, Ziyu; Toci, Guido; Pirri, Angela; Patrizi, Barbara; Li, Jinbang; Hu, Zewang; Wei, Jiabei; Pan, Hongming; Xie, Tengfei; Vannini, Matteo; Li, Jiang
Abstract: In this article, 5 at.% Yb:Lu2 O3 transparent ceramics were fabricated by vacuum sintering combined with hot isostatic pressing (HIP) posttreatment using co‐precipitated nano‐powders. The influence of precipitant molar ratio, ammonium hydrogen carbonate, to metal ions (AHC/M 3+, R value) on the properties of Yb:Lu2 O3 precursors and calcined powders was investigated systematically. It was found that the powders with different R value calcined at 1100°C for 4 hours were pure cubic Lu2 O3 but the morphologies of precursors and powders behaved differently. The opaque samples pre‐sintered at 1500°C for 2 hours grew into transparent ceramics after HIP posttreatment at 1750°C for 1 hour. The final ceramic with R = 4.8 showed the best optical quality with the in‐line transmittance of 79.7% at 1100 nm. The quasi‐CW laser operation was performed at 1034 nm and 1080 nm with a maximum output power up to 8.15 W as well as a corresponding slope efficiency of 58.4%.